Challenges of democratic governance in Latin America and the Caribbean : sounding an alarm - Dominguez, Jorge (Inter-American Dialogue WashingtonUS, 1994)
Focuses on problems and difficulties facing democratic institutions in the Americas, such as ineffective justice systems; lack of policy continuity among successive governments; weak and unrepresentative political parties; increasing crime levels; and, the exclusion of marginalised groups from political power.